Navigating Financial Performance of the MENA Region Energy Sector: The Interplay of Working Capital and Leverage - Elgayar, Ahmed; Serag, Sameh; Metawa, Noura (International Journal of Economics and Financial Issues, 2024)
This research delves into the influence of leverage considering potential outcomes within operational funds concerning the fiscal implications of the energy industry within the middle east and north Africa region. The research employed an empirical approach by collecting secondary data from the MENA region's energy sector between 2018 and 2022. To achieve this, the study formulated three hypotheses and utilized the empirical random panel data model. The investigative results affirm the validity of all three hypotheses. Additionally, they provide insights into the relationships among the variables in these hypotheses. Particularly noteworthy is the fact that certain results from the hypotheses contradict the expected theoretical impact. The article suggests that future researchers should delve into additional factors influencing firm performance, recognizing that diverse variables may yield varied outcomes. Broadening the study's scope by incorporating different timeframes and a more diverse array of firms could enhance the overall representativeness of research findings. Expanding this inquiry beyond the energy sector to encompass various industries might offer a comprehensive understanding of how working capital affects firm performance across distinct economic sectors. Subsequent empirical studies are advised to consider global health crises, political events, and other socio-economic developments in the MENA region. Examining events such as the COVID-19 pandemic and ongoing geopolitical conflicts like the Russian-Ukrainian and Israeli-Palestinian conflicts could illuminate how such incidents impact of the association among cash reserve, leverage, and company efficacy. To gain deeper insights into the causal distinctions among financial resources, and production form the company, researchers might investigate bidirectional results between each pair of variables using Granger causality tests. The findings from the present study are pertinent for energy sector companies, policymakers, and academia. Future research endeavors could focus on scrutinizing how the implications of operating funds on company procedures change when moderated by additional factors related to macroeconomics, providing practical insights for decision-makers.